BEHAVIOURE STUDY OF THE ASSOCIATION BETWEEN ACID-BASE INDICATORS IN ACIDIC MEDIUM BY USING SPECTROSCOPY TECHNIQUE - Hemdan, Sokaina Saad; Al Jebaly, Asma Mansur; Ali, Fatma Khairallah (Journal of natural sciences, life and applied sciences, 2018)
The association behavior between Acid-Base indicators in buffered aqueous solution (pH = 4) has been studied by UV–Vis spectroscopy technique at room temperature. The spectroscopic results show that association are formed evidenced by highly red shift to  lmax = 485nm and large hypo-chromic shift in absorbance signal upon addition of ago dye. The electronic absorption spectra represented by broadening bands and lack of isosbestic point that indicate of formation of higher order dye aggregates from the type J-aggregate as results as change of the pH of the medium were discussed according to exciton kasha theory.
Keywords: Spectrum; Electronic Absorption; Acid-Base Indicators; Lack of Isosbestic Point; Higher Aggregates; Buffer Solution